Conformational Effects of a Cancer-Linked Mutation in Pri-miR-30c RNA. Issue 18 (30th September 2022) - Jones, Alisha N.; Walbrun, Andreas; Falleroni, Fabio; Rief, Matthias; Sattler, Michael
Graphical abstract: Highlights: Sequence variations of pri-miRNAs can affect protein interactions and processing. Wildtype (WT) and a G/A variant of pri-miR-30c RNA adopt similar structures. The G to A mutation disrupts a kissing hairpin structure native to the WT RNA. The dimeric kissing hairpin of WT pri-miR-30c sequesters a binding site for hnRNP A1. The monomeric G/A variant favors hnRNP A1 binding and processing. RNA sequence variations influence structure and function of pri-miRNAs. Abstract: MicroRNAs (miRNAs) are small, noncoding RNAs that mediate post-transcriptional downregulation of specific target genes. These transcripts are the products of a two-step processing pathway; primary miRNAs (pri-miRNAs) are processed by Drosha into individual precursor miRNA (pre-miRNA) hairpins, which are subsequently processed by Dicer into mature miRNAs. Single nucleotide polymorphisms (SNPs) that occur in pri-miRNAs, pre-miRNAs and mature miRNAs have been shown to affect the processing of specific target genes by modulating Drosha and Dicer processing or interactions with RNA binding proteins (RBPs). Using NMR and single-molecule optical tweezer experiments, we have investigated the conformational effects of a cancer-linked G/A mutation in the terminal loop of pri-miR-30c RNA, and how this influences binding by the SRSF3 and hnRNP A1 RBPs, which are implicated in its processing. Our results reveal that the wildtype and G/A variant pri-miR-30c RNAs adopt very similar elongated stem-loop structures, both of which are bound by SRSF3. However, while both wildtype and G/A pri-miR-30c RNAs can form dimeric kissing hairpin structures, the G to A mutation results in partial destabilization of the dimer in the variant transcript. This promotes recognition and binding by hnRNP A1, an RBP that enhances pri-miR-30c processing. Our data provide structural insight into the conformational effects of a G/A mutation in pri-miR-30c RNA and how this could affect processing and promote cancer.